Metastasis to the ureter as the first manifestation of occult pulmonary adenocarcinoma. Case report and review of the literature - Ciarka, Aleksandra; Skowronek, Filip; Kunc, Michal; Bieńkowski, Michał; Pęksa, Rafał (Contemporary Oncology/Współczesna Onkologia, 2023)
Lung cancer is a major epidemiological threat worldwide, which commonly metastasizes to distant sites. Often, the presence of metastasis is the first manifestation of lung cancer. Some of the most common sites for lung cancer metastasis are bones, adrenal glands, liver, brain, and lungs. However, metastases to unusual locations pose a diagnostic and therapeutic challenge. We present a case of a 74-year-old woman in whom the first manifestation of lung cancer was metastasis to the right ureter. We also analyse the available literature on lung cancer metastases to the ureter, taking into account the possible mechanisms of their spread in the ureter.